Gingival squamous cell carcinoma mimicking as a desquamative lesion - Keshava, Abbayya (J Indian Soc Periodontol, 2016)
Oral squamous cell carcinoma (SCC) is the most frequently encountered neoplasm in the oral cavity, which accounts for more than 90% of all cancers. Except for carcinoma of the lip vermilion, the most common sites of oral SCC are the tongue and floor of mouth, followed at a lower frequency by the soft palate, gingiva, and buccal mucosa. Clinically, it may be misdiagnosed because of its variable appearances. This case report presents a case of well-differentiated SCC of gingiva. A 48-year-old male patient reported to the Department of Periodontology, School of Dental Sciences, Karad, with a 1-year history of burning sensation and painful lesion on the gingiva from 35 to 37 (mandibular) regions. On clinical examination, desquamated gingival lesion was seen with no purulent exudation. Clinical characteristics and differential diagnosis indicated the lesion for an excisional biopsy. Histopathological examination confirmed the lesion to be a well-differentiated SCC. The patient was referred for the treatment consisting of surgical excision of the lesion. Since an early diagnosis and treatment was possible in this case, it resulted in a good prognosis. In these instances, dentist plays an important role in early detection of gingival SCC.